Penerapan Alat Pilah Olah Sampah Mandiri Terintegrasi (PLASMA-T) untuk Pengelolaan Sampah di Desa Karanglewas - Abednego Dwi Septiadi; Yudha Islami Sulistya; Nisrina Hanifa Setiono; Laurensius Windy Octanio Haryanto; Galih Putra Pamungkas (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The waste problem in Karanglewas Village, Kutasari District, Purbalingga Regency, continues to increase alongside agricultural, trade, and MSME activities, while the management system remains conventional, without sorting, resulting in environmental pollution and limited landfill capacity. This community service program aims to implement the Integrated Independent Waste Sorting and Processing Tool (PLASMA-T) as an innovative solution that processes organic waste into compost and melts plastic waste into paving blocks that are useful and economical. The activities are carried out in stages, including problem identification, socialization, technical training, operational trials, evaluation of results, and the handover of the equipment to the Mitra Sejahtera TPS, with ongoing assistance so that the community can operate the equipment independently. The expected outcomes include a reduction in waste volume at the TPS, increased community awareness and skills in waste management, and the creation of new business opportunities through compost and paving block products. Thus, this program not only addresses environmental issues but also strengthens the village's circular economy and has the potential to serve as a model for other regions.